Dampak Stress Kerja Terhadap Kesejahteraan Mental Anggota Kepolisian - Shabrina Shabrina; Elisabet Mediana Putri; Hildegardis Patricia Loko Wewa; Salwa Tazkia F; Tugimin Supriyadi (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
In general, the performance of police officers will not always increase, but sometimes the performance of police officers also decreases due to excessive work stress. This gives rise to various impacts, one of which will have an impact on the mental well-being of police officers. The aim of this research is to determine the impact of work stress on the mental well-being of police officers. This type of research is qualitative research, while for data collection this research uses literature studies. The results of this research show that work stress has a social and psychological impact on the mental well-being of individual police officers who carry out their duties. The importance of managing workload and social support from superiors and co-workers is one of the influential factors in managing the impact of work stress and increasing job satisfaction.